Sustaining Innovation - Nadig, Toni (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
I’ve been asked by the organisers of this event to speak about the subject of change management. I can imagine that a few of you in the audience have had experience with this ‚bugaboo’ called change. It’s certainly nothing new, in fact it’s become a standard companion in most industry sectors. With a constant metamorphosis in external environments around us there is a real and pressing need to adjust our organisations, their structures and resources to changing conditions. And then to change again. And again.